Prevention of inflammatory complications at the postembolization period in women with uterine leiomyomas - Калугіна, Л. В.; Татарчук, Т. Ф; Косей, Н. В.; Васильченко, Л. А. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
Modern views on the pathogenesis of uterine fibroids account for the role of chronic inflammation in tumor growth that makes relevant the question of the drugs choice for prophylactic antibiotic therapy after organ-saving operations. The study to optimize management of the postoperative period after uterine artery embolization was performed. The study involved 63 women aged 24 to 38 years who underwent uterine artery embolization for node uterine fibroids. Women were randomly divided into 2 groups: the main group consisted of 30 women who intake ornidazole, ciprofloxacin, fluconazole and analgesic therapy; control group consisted of 33 patients who received metronidazole, ciprofloxacin, fluconazole and analgesic therapy. This study demonstrated a high efficiency sof supplement а combination antibiotic therapy by ornidazole to optimize management of the postembolization period and contributes to the restoration of female reproductive function.